The Role Of The School Environment In Early Childhood Language Development - Febriani, Afifah; Oktavia, Rita; Dwi Utami, Rahmi; Satrial, Ardi (Journal of Islamic Early Childhood Education, 2025)
Language development in early childhood is a fundamental aspect that influences children's communication, cognitive, and social abilities. The school environment plays an important role in supporting the language acquisition process through educational interactions, adequate facilities, and interactive learning methods. This research was conducted at Yappega Gantung Ciri Islamic Kindergarten, Solok Regency, which is known for its integration of character-based learning and local wisdom. This study aims to describe the forms of communication and social interactions that influence early childhood language development, as well as to identify the factors that influence it. The method used is field research with a qualitative descriptive approach. Data were obtained through observation, interviews, and documentation with the principal and four teachers using a purposive sampling technique. The results of the study indicate that children's language development is influenced by: (1) the provision of a stimulus-rich learning environment such as a reading corner and interactive media; (2) the implementation of active learning strategies such as role-playing, storytelling, and charades; (3) positive social interactions between teachers and students; (4) strengthening local cultural values through the use of the Minang language in learning activities; and (5) parental support through parenting activities. In addition, internal factors such as children's interests and character, as well as external factors such as media and gender also influence the language development of early childhood.